Association of geriatric nutritional risk index with the risk of osteoporosis in the elderly population in the NHANES - Huang, Wei; Xiao, Yingqi; Wang, Hongwei; Li, Kaixiang (Frontiers in Endocrinology, 2022)
Background: Osteoporosis is common in the elderly, and malnutrition is considered a major risk factor for osteoporosis. This study investigated the relationship between the Geriatric Nutrition Risk Index (GNRI) and osteoporosis based on a large cross-sectional study of the National Health and Nutrition Examination Survey (NHANES). Methods: We included 7405 older adults from NHANES (2005 to 2018) and divided them into the High-GNRI and Low-GNRI groups based on GNRI levels to compare the prevalence of osteoporosis among the two groups. A multi-factor logistic regression analysis was used to determine whether GNRI was an independent risk factor for osteoporosis. Spearman's rank correlation coefficient was computed to investigate the linear relationship between geriatric nutritional risk index (GNRI) and bone mineral density (BMD) T-score. Finally, a generalized additive model (GAM) revealed whether there was a non-linear relationship between GNRI and osteoporosis. Results: The prevalence of osteoporosis was higher in the Low-GNRI group than those in the High-GNRI group (12.2% vs. 8.2%; P = 0.001). Similarly, the femoral neck BMD T-scores (-1.09 ± 1.42 vs. -0.91 ± 1.31; P = 0.003). However, there was no significant difference between Low-GNRI group and High-GNRI group in lumbar BMD T-scores (1.700 ± 1.69 vs 1.85 ± 1.72; P>0.05). The multi-factor logistic regression analysis identified low GNRI as an independent risk factor for osteoporosis (OR: 1.544; 95% CI: 1.179-2.022; P < 0.001). Besides, GNRI showed a positive linear correlation (P < 0.001) with femoral neck BMD T-scores in older adults, with a progressive trend towards higher BMD as GNRI increased. By contrast, there was no linear correlation between GNRI and lumbar BMD T-score (P = 0.978). Lastly, the dose response curve revealed the non-linear negative correlation between GNRI and the risk of osteoporosis in the elderly (non-linear P < 0.001). With the increase of GNRI, the risk of osteoporosis gradually decreased, especially when GNRI was greater than 100, the downward trend was more significant. Conclusion: GNRI is an independent risk factor for osteoporosis in the elderly and is negatively and non-linearly associated with the risk of osteoporosis in the elderly population.